Biological Roles of Nontypeable Haemophilus influenzae Type IV Pilus Proteins Encoded by the pil and com Operons - Carruthers, Michael D. (American Society for Microbiology, 2012)
We previously demonstrated that one or more products of the genes in the pil and com gene clusters of the opportunistic human respiratory pathogen nontypeable Haemophilus influenzae (NTHI) are required for type IV pilus (Tfp) biogenesis and function. Here, we have now demonstrated that the pilABCD and comABCDEF gene clusters are operons and that the product of each gene is essential for normal pilus function. Mutants with nonpolar deletions in each of the 10 pil and com genes had an adherence defect when primary human airway cells were used as the target. These mutants were also diminished in their ability to form a biofilm in vitro and, additionally, were deficient in natural transformation. Collectively, our data demonstrate that the product of each gene within these operons is required for the normal biogenesis and/or function of NTHI Tfp. Based on the similarity of PilA to other type IV pilins, we further predicted that the product of the pilA gene would be the major pilin subunit. Toward that end, we also demonstrated by immunogold labeling and mass spectrometry that PilA is indeed the majority type IV pilin protein expressed by NTHI. These new observations set the stage for experiments designed to dissect the function of each of the proteins encoded by genes within the pil and com gene clusters. The ability to characterize individual proteins with vital roles in NTHI colonization or pathogenesis has the potential to reduce the burden of NTHI-induced diseases through development of a Tfp-derived vaccine or a pilus-directed therapeutic.